Thermodynamic analysis and thermogravimetric investigation on chemical looping gasification of biomass char under different atmospheres with Fe2O3 oxygen carrier. (1st November 2015) - Huang, Zhen; He, Fang; Zhu, Huangqing; Chen, Dezhen; Zhao, Kun; Wei, Guoqiang; Feng, Yipeng; Zheng, Anqing; Zhao, Zengli; Li, Haibin
Highlights: Chemical looping gasification (CLG) of char under various atmospheres is studied. The carbon conversion of char attained to 40.8% in CLG even under inert atmosphere. Oxidizing agents can promote the char conversion due to enough oxygen sources. A reactivity of different oxygen sources is followed by NiO > H2 O > Fe2 O3  > CO2  > Al2 O3 . Fe2 O3 phase is mainly reduced into Fe3 O4 phase under various atmospheres. Abstract: Chemical looping gasification (CLG) is viewed as a promising gasification technology because gas phase oxygen of gasifying medium can be replaced by lattice oxygen of oxygen carrier. In the present work, the reactivity of biomass char with Fe2 O3 oxygen carrier under different atmospheres was detailed investigated through the thermodynamic and thermo-gravimetric analysis. The Fe2 O3 was almost completely reduced into metallic iron when the reaction temperature exceeded 1000 °C, but the carbon conversion of char only attained to 40.80% due to the lack of oxygen source under inert atmosphere. However, the carbon conversion of char apparently increased and the oxygen conversion of oxygen carrier dramatically decreased under oxidizing atmosphere (CO2, or H2 O). It is attributed to the fact that oxidizing agents can supply oxygen sources to promote char conversion as well as to alleviate the reduction of oxygen carrier. These thermodynamic predictions were confirmed by TGA tests, where the char was fully converted into gas under CO2 or H2 O atmosphere because of enough oxygen sources but a low carbon conversion was obtained under inert atmosphere. TGA results further indicated that the reactivity of char with oxygen carrier under steam atmosphere is much higher than that under CO2 atmosphere and the Fe2 O3 phase is mainly reduced into Fe3 O4 phase in all the tests. Additionally, several other different carriers (Al2 O3, NiO-modified iron ore and NiO) were employed to compare the reactivity of iron ore as well. The order of reactivity is speculated as follows: Pure oxygen ≈ NiO > H2 O > Iron ore > CO2  > Al2 O3 . The reduced oxygen carrier can recover entire lattice oxygen [O] to its initial state under air atmosphere. Therefore, it suggests that the Fe2 O3 material used as an oxygen carrier can be recycled in the process of char CLG.